Bilateral Fitting of Bone-Anchored Hearing Devices: Speech Recognition and Sound Localization - Ueda, Cynthia Harumi Yokoyama; Jardim, Isabela de Souza; Bento, Ricardo Ferreira; Soares, Renata Marcial (International Archives of Otorhinolaryngology, 2025)
Bilateral fitting of bone-anchored hearing devices (BAHD) remains a contentious topic, as the use of a single device can direct sound to both cochleae. However, the interplay of interaural attenuation and time delay may result in different responses in each ear; thus, greater challenges for unilateral BAHD users.To assess the auditory performance of BAHD users with unilateral and bilateral fitting regarding speech recognition in silence and noise and sound localization.Cross-sectional study. Unilateral BAHD users treated at a Brazilian public hospital underwent a speech recognition test, containing a list of monosyllables at 65dBSPL in silence and noise (S/N ratio = 0dB). The sound localization test employed eight speakers arranged at 45° distance. A recorded trisyllabic word served as the stimulus. For bilateral fitting, an elastic band with a device similar to the implant was used; patients underwent the same tests under identical conditions.Sixteen patients were assessed (mean age = 24.2 years). The average monosyllable recognition in silence rate was 71.5% in unilateral fitting and 78.2% in bilateral fitting. In noise, 61% in unilateral fitting and 72.2% in bilateral fitting. The mean angular deviation for the sound localization test was 80.48° in unilateral fitting and 68.08° in bilateral fitting. The bilateral fitting outcomes were better for all tests.Users with bilateral BAHD fitting had better outcomes for speech recognition and sound localization.
Keywords: bilateral hearing loss; hearing aids; bone-anchored prosthesis; bone conduction; correction of hearing impairment; speech discrimination tests